Caracterización de la actividad pesquera en las principales zonas de desembarque de la ciudad de Yurimaguas – Provincia de Alto Amazonas 2020 - Vargas Peña, Maricarmen (2022)
The present research work was carried out between the months of November 2020 to March 2021, with the objective of characterizing the fishing activity of the main landing areas of the city of Yurimaguas - province of Alto Amazonas; The study focused on the registration of fishing landing information, obtained through the application of evaluation instruments to artisanal fishermen, the evaluation points for fishermen were the main fish sales areas such as the "La Loretana" berth, " San Miguel”, “La Boca”, “La Ramada” and the “Abel Guerra” dock. The results of the investigation show that the fishing zone of the Nucuray river represents 23.04% of the landing volume of the city of Yurimaguas, followed by the Marañón with 17.55% and the Pastaza river with 4.90%; Likewise, the fishing gear most used by artisanal fishermen are the sling net, which represents 35.66%, followed by the trawl net, which represents 33.24% of the total catch; The CPUE in the Nucuray River is represented by 1,552 kg/trip, followed by the Marañón River with 1,256 kg/trip, while the lowest value corresponds to the Dos de Mayo fishing zone with a contribution of 752 kg/trip ; in relation to the most representative species, these are Prochilodus nigricans (24.17%) and Megaleporinus trifasciatus (20.21%), followed by Calophysus macropterus (8.92%); In addition, the Characiformes order represents the taxa with the highest frequency in the captures, with 72.35%, followed by the Siluriformes order with 18.46%; in relation to the capture sizes, within the framework of the regulated species, the maiden is captured below the minimum size allowed and the boquichico presented values above the minimum capture size. A total fishing landing of 242,520 Kg was obtained with 51 vessels operating. The fishing activity is carried out through the use of wooden boats of 7-10 meters in length with an average load capacity of 1,230 kg.